The relationship between effective human resources management practices and job satisfaction among lecturers in UiTM / Sofiadora Drahman - Drahman, Sofiadora (2013)
The aim of the study is to examine the relationship between Human Resources Management Practices and job satisfaction among lecturers in UiTM. This study looked into lecturers' perception towards Human Resources Management Practices. Besides that, it also investigated the level of lecturers' job satisfaction and attempted to identify their suggestions to improve Human Resources Management Practices in higher education. Two faculties involved in this study namely Faculty of Education and Academy of Language Studies participated in UiTM. The questionnaires were distributed to a total of 120 randomly selected lecturer respondents and 77 questionnaires have been returned, however only 76 questionnaires usable for this study. Data was analyzed using descriptive and correlational inferential statistic. The findings revealed that the lecturers' moderately perceived the overall Human Resources Management Practices. Among the entire dimensions, the highest was the recruitment and selection dimension. The findings also showed that the level of lecturers' job satisfaction was at moderate level. Among these subscales of job satisfaction, growth received the highest level by the lecturer respondents. This study also indicated the dimension of Human Resources Management Practices that correlate with job satisfaction namely working environment, performance appraisal, compensation practices, promotion practices and overall Human Resources Management Practices. Besides that, there were three dimensions of Human Resources Management Practices namely orientation, training and recruitment and selections were not correlated with overall job satisfaction. Overall, the findings have implications to the lecturers, Ministry of Higher Education, leaders and policy makers in the public universities in Malaysia. Hopefully the findings of this research would provide useful recommendations for the improvement of human resources management in higher education institutes.